Language policies and practices in wholly owned foreign subsidiaries: A recontextualization perspective - Peltokorpi, Vesa; Vaara, Eero (Journal of International Business Studies, 2012)
This study adopts a recontextualization perspective on language policies and practices in wholly owned foreign subsidiaries. Drawing on a field study of 101 subsidiaries in Japan, we develop a contingency model that distinguishes between four different types of recontextualization with characteristic language policies and practices: developing/locally adaptive, developing/globally integrated, established/locally adaptive, and established/globally integrated. Our analysis shows how each of these four types is accompanied by specific problems and challenges. In particular, it elucidates five important aspects of language implementation: (1) the emergence of language praxis from the interplay of headquarters strategies and local responses; (2) the hybridization of language practices; (3) the central role of key actors such as subsidiary presidents in recontextualization; (4) the pervasive power implications of language policies and practices; and (5) the multifaceted implications for strategic human resource management. By so doing, our analysis opens up new avenues for context-specific and practice-oriented studies of language in multinational companies.